The Effect of Using Picture Stories Media and Learning Activities Towards Students’ Ability in Writing - Nur Aini; Surastina Surastina; Frieska Maryova; Febriyanti Febriyanti (Master Program in Indonesian Language Education and The Institute for Research and Community Service STKIP PGRI Bandar Lampung, 2022)
The purpose of this study was to analyze: (1) the difference in the average of students’ ability in writing paragraphs using pictorial story media and those without using pictorial media. (2) the influence of students who have high learning activities using picture stories media on writing skills is better than students who have high learning activities without using picture stories media. (3) the average score of students’ ability in writing paragraphs with high learning activities who use the picture stories is higher than those who do not use picture stories media. (4) the average score of students’ ability in writing paragraphs with low learning activities who use the picture stories is higher than those who do not use picture stories media. The method used in this research is the experimental method. The results of this study indicate that learning activities and picture stories media have a positive effect towards the students’ ability in writig paragraphs. The interaction of students who have high learning activities and are taught using picture stories media has the highest average value in writing paragraph ability, that is 16.74. Furthermore, the average scores of students with low learning activities and being taught with picture stories media is 15.03, then students with high learning activities and being taught without media is 10.67, and finally the average score of students who have low learning activities and are taught without picture stories media is 10,13.